Ecotheology-Based Christian Religious Education and Its Impact on Generation Z’s Ecological Awareness - Susanti Embong Bulan (Shift Key : Jurnal Teologi dan Pelayanan, 2026)
This study examines the integration of ecotheology into Christian Religious Education and its potential impact on Generation Z’s ecological awareness. Using a qualitative approach with a systematic literature review, this research synthesizes interdisciplinary studies in environmental education, theology, and generational learning. The findings reveal that environmental education alone is insufficient to foster consistent pro-environmental behavior due to the persistent value–action gap. In contrast, ecotheology introduces moral and spiritual dimensions that strengthen internal motivation and ethical responsibility. Furthermore, ecotheology-based education aligns with Generation Z’s learning characteristics, particularly participatory, contextual, and experiential approaches. This study proposes an integrative conceptual framework that connects cognitive, affective, spiritual, and behavioral dimensions in ecological learning. However, as a literature-based study, its findings remain conceptual. Future research is recommended to empirically test this framework through experimental designs, case studies in schools and churches, and longitudinal studies across diverse cultural and educational contexts.